1988
DOI: 10.1557/jmr.1988.0787
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium oxide crystal phase: The role of the pH and time to attain the final pH for precipitation of the hydrous oxide

Abstract: Precipitated hydrous zirconium oxide can be calcined to produce either a monoclinic or tetragonal product. It has been observed that the time taken to attain the final pH of the solution in contact with the precipitate plays a dominant role in determining the crystal structure of the zirconium oxide after calcination at 500 °C. The dependence of crystal structure on the rate of precipitation is observed only in the pH range 7–11. Rapid precipitation in this pH range yields predominately monoclinic zirconia, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
86
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 22 publications
3
86
1
Order By: Relevance
“…The resulting product was washed to a negative test for chloride ion (ca. 10 washings) and then calcined at 500 °C for 200 h. [11][12] Samples D and E were prepared in a manner similar to that reported by Benedetti et al 21 Sample D, which corresponds to sample III in Ref. 21, was washed twice while sample E (sample II in Ref.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The resulting product was washed to a negative test for chloride ion (ca. 10 washings) and then calcined at 500 °C for 200 h. [11][12] Samples D and E were prepared in a manner similar to that reported by Benedetti et al 21 Sample D, which corresponds to sample III in Ref. 21, was washed twice while sample E (sample II in Ref.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The material precipitated at a pH of 2.95 was predominantly the tetragonal phase following a 4 hour heating period; however, during the 200 hour heating period there was a gradual transformation to the monoclinic phase. 41 Precipitations were also carried out at a pH of 10.4 by the slower addition of base. In this slower precipitation procedure, a calculated amount of base was added dropwise to a stirred zirconium salt solution at a rate to produce the desired pH at a targeted time.…”
Section: Precipitation Of Hydrous Zirconiamentioning
confidence: 99%
“…48,49 Hydrolytic polymerization of ZrOCl 2 ·8H 2 O solutions produces a hydrated amorphous gel of ZrO 2 , which can be transformed into crystalline phases such as monoclinic and tetragonal ZrO 2 on heating, with the phase formed dependent on the precipitation conditions. 49 It is reported that the crystal structure of ZrO 2 is dependent on the pH of the precipitation solution and the time taken to attain this pH, although the thermodynamic stable phase of crystalline ZrO 2 is monoclinic at room temperature. 49,50 Tetragonal ZrO 2 was found to be formed more effectively in precipitation solutions of higher pH and with slower precipitation rates.…”
mentioning
confidence: 99%
“…49 It is reported that the crystal structure of ZrO 2 is dependent on the pH of the precipitation solution and the time taken to attain this pH, although the thermodynamic stable phase of crystalline ZrO 2 is monoclinic at room temperature. 49,50 Tetragonal ZrO 2 was found to be formed more effectively in precipitation solutions of higher pH and with slower precipitation rates. Further studies also propose that the tetragonal phase can be stabilized against transformation to monoclinic if the particle size is less than 30 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation